Capital markets and financial intermediation in the Baltics - Schipke, Alfred; International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2004)
Capital Markets and Financial Intermediation in The Baltics analyzes the financial systems of the three countries and discusses some of their unique characteristics. The study also examines current distortions of the systems and discusses whether or not the Baltics should move from an almost exclusively bank-based system to one that relies more on capital markets. In the process, it addresses issues of corporate governance and regional integration.
"...Based on a staff background paper for the 2003 Article IV consultations between the International Monetary Fund and the Republic of Estonia, the Republic of Latvia, and the Republic of Lithuania" -- v.
Includes bibliographical references (p. 35-38).
aid 18/05/2018, ijb 08/04/2019
Ref.
Keywords: Capital market; Banks and banking, Foreign; Intermediation (Finance); Economic history; Membership requirements; European Union; Baltic States